Assessing user perspectives on clinical pharmacogenomics consultation documentation: a user-centered evaluation - Desai, Nina; Ravindra, Namratha; Hall, Bradley; Al Alshaykh, Hana; Lemke, Lauren; Eken, Eda; Cicali, Emily J.; Wiisanen, Kristin; Cavallari, Larisa H.; Nguyen, Khoa A. (Frontiers in Pharmacology, 2024)
The University of Florida Health Precision Medicine Program plays a crucial role in delivering pharmacogenomics (PGx) result notes to providers who request PGx testing. Despite this, there is currently a lack of a formal assessment of provider needs and established best practice design principles to guide the ongoing development of PGx result notes. This study aims to enhance the content and format of the PGx consult note at UF Health by incorporating valuable feedback from healthcare providers. Through in-depth user sessions involving 11 participants, we evaluated the usability of our consult note template. While overall satisfaction with the content was noted, specific sections, including those addressing phenoconversion and the medication list, were identified for revision to enhance clarity based on insightful provider feedback.